Perancangan Sistem Otomatisasi Peternakan Ayam Broiler Berbasis Internet Of Things - Hendra; Maya Indriana; Nurul Tri Artika; Ricca Ismayani; David Jumpa Malem Sembiring; Melvarina Tamba (Prodi Teknik Informatika (S1) Institut Teknologi dan Bisnis Indonesia, 2023)
Livestock is an activity to breed and cultivate livestock to get the benefits and results of these activities. Therefore we need a system that is able to help control feeding and drinking and regulate temperature humidity . The technology that can be used is internet of things technology which is a technology that allows physical objects to communicate with each other via the internet. This farm system uses 4 sensors that function to detect temperature, light, feed availability, and drinking availability. and using Arduino 328 as a microcontroller which functions to control an input output from a system designed to process input data from sensors. the test results show that the system is able to provide information through the android application if a vacancy is detected in the feed and drink place as well as temperature humidity control.